FAKTOR – FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PEMERINTAH KABUPATEN/KOTA DI PROVINSI SUMATERA SELATAN TAHUN 2012-2015 - Evada Dewata; Nyayu Miftahul Ilmiyyah; Sarikadarwati Sarikadarwati (Politeknik Negeri Batam, 2017)
The purpose of this research was to determine factors that influence the financial performance of regency/city in the south of Sumatera province 2012-2015. Independent variable of this research was audit opinion, legislative, intergovernmental revenue, size, leverage, and the cluster of local financial capacity. The samples used were as many as 15 regencies/cities using purposive sampling method. Data were collected by using the method of documentation. This research result showed that audit opinion, legislative, intergovernmental revenue, size, leverage, and the cluster of local financial capacity gave a significant influence on the financial performance of regency/city that was measured based on the independence rate ratio. Partially, audit opinion, legislative, size, leverage, and cluster of local financial capacity variables did not give a significant influence on the financial performance of regency/city but Intergovernmental revenue variable gave a negative significant influence on the financial performance of city.